2005
DOI: 10.1161/circulationaha.104.507897
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Spinal Cord Stimulation Reduces the Risk of Ischemic Ventricular Arrhythmias in a Postinfarction Heart Failure Canine Model

Abstract: Background-Thoracic spinal cord stimulation (SCS) is a promising therapy in treating refractory angina. This study was designed to investigate SCS with regard to the risk of arrhythmias during myocardial ischemia and its cardiac electrophysiological effects. Methods and Results-We studied 22 dogs with healed anterior myocardial infarction (MI) and superimposed heart failure (HF) induced by rapid ventricular pacing. SCS was applied at the dorsal T 1 -T 2 segments of the spinal cord (at 50 Hz, 0.2 ms) for 15 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(95 citation statements)
references
References 33 publications
6
85
1
3
Order By: Relevance
“…Bradycardias and atrial arrhythmias can be neuronally induced by mediastinal nerve stimulation in dogs (Cardinal et al, 2006). SCS significantly suppresses these arrhythmias provoked by ischemia (Issa et al, 2005;Cardinal et al, 2006). This effect is blocked after bilateral stellectomy (Cardinal et al, 2006).…”
Section: Intrinsic Cardiac Nervous System Related Mechanism-mentioning
confidence: 99%
“…Bradycardias and atrial arrhythmias can be neuronally induced by mediastinal nerve stimulation in dogs (Cardinal et al, 2006). SCS significantly suppresses these arrhythmias provoked by ischemia (Issa et al, 2005;Cardinal et al, 2006). This effect is blocked after bilateral stellectomy (Cardinal et al, 2006).…”
Section: Intrinsic Cardiac Nervous System Related Mechanism-mentioning
confidence: 99%
“…Issa et al 91 demonstrated that thoracic spinal cord stimulation at T1-T2 segments reduced the incidence of ventricular tachyarrhythmias in canine model of ischemic cardiomyopathy from 59% to 23% when applied during myocardial ischemia. Furthermore, they observed a simultaneous decrease in heart rate and reduced systolic blood pressure, consistent with the antisympathetic effects of spinal cord stimulation.…”
Section: Selective Sympathetic Blockadementioning
confidence: 99%
“…57 Issa et al 58 observed a significant decrease in VT and VF in a canine heart failure model that was exposed to transient ischaemia. In this model, SCS reduced VT/VF incidence from 59 % to 23 % in the setting of acute ischaemia.…”
Section: Spinal Cord Stimulation and Ventricular Electrophysiologymentioning
confidence: 98%